Characterization of the complete chloroplast genome of Suaeda salsa (Amaranthaceae/Chenopodiaceae), an annual succulent halophyte - Qu, Xiao-Jian (Mitochondrial DNA B Resour, 2019)
Suaeda salsa, an annual succulent halophytic herb, is one of the major halophyte widely distributed in both saline inland and the intertidal zone. In this study, we report the complete chloroplast genome (plastome) of S. salsa. The plastome was 151,642 bp in length and comprises a large single-copy region (83,502 bp), a small single-copy region (17,780 bp), and a pair of inverted repeats (25,180 bp). It encodes 113 unique genes, including 79 protein-coding genes (PCGs), 30 tRNAs, and four rRNAs. The overall GC content of this plastome was 36.4%. Phylogenomic analysis based on 20 plastomes revealed that S. salsa was closely related to S. malacosperma.